Effect of baseline CD4 cell counts on the clinical significance of short-term immunologic response to antiretroviral therapy in individuals with virologic suppression. - Moore, David M; Harris, Ross; Lima, Viviane; Hogg, Bob; May, Margaret; Yip, Benita; Justice, Amy; Mocroft, Amanda; Reiss, Peter; Lampe, Fiona; Chêne, Geneviève; Costagliola, Dominique; et al. (Journal of acquired immune deficiency syndromes (1999), 2009)
Achieving virologic suppression is a clear therapeutic goal for patients receiving combination antiretroviral therapy (cART). However, the effects of immunologic responses, whether measured as CD4 count changes from baseline or CD4 counts at follow-up, in patients with virologic suppression, have not been clearly established.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Cohort Studies; Drug Administration Schedule; Female; HIV Infections; Humans; Male; Middle Aged